Brief Sensory Training Narrows the Temporal Binding Window and Enhances Long-Term Multimodal Speech Perception - Zerr, Michael; Freihorst, Christina; Schütz, Helene; Sinke, Christopher; Müller, Astrid; Bleich, Stefan; Münte, Thomas F.; Szycik, Gregor R. (Frontiers in Psychology, 2019)
Our ability to integrate multiple sensory-based representations of our surrounding supplies us with a more holistic view of our world. There are many complex algorithms our nervous system uses to construct a coherent perception. An indicator to solve this ‘binding problem’ are the temporal characteristics with the specificity, that environmental information has different propagation speeds (e.g. sound and electromagnetic waves) and sensory processing time and thus the temporal relationship of a stimulus pair derived from the same event must be flexibly adjusted by our brain. This tolerance can be conceptualized in the form of the cross-modal temporal binding window (TBW). Several studies showed the plasticity of the TBW and its importance concerning audio-visual illusions, synesthesia, as well as psychiatric disturbances. Using three audio-visual paradigms, we investigated the importance of length (short vs. long) as well as modality (uni- vs. multimodal) of a perceptual training aiming at reducing the TBW in a healthy population. We also investigated the influence of the TBW on speech intelligibility, where participants had to integrate auditory and visual speech information from a videotaped speaker. We showed that simple sensory trainings can change the TBW and are capable of optimizing speech perception at a very naturalistic level. While the training-length had no different effect on the malleability of the TBW, the multisensory trainings induced a significantly stronger narrowing of the TBW than their unisensory counterparts. Furthermore, a narrowing of the TBW was associated with a better performance in speech perception, meaning, that participants showed a greater capacity for integrating information from different sensory modalities in situations with one modality impaired. All effects persisted at least seven days. Our findings show the significance of multisensory temporal processing regarding ecologically valid measures and have important clinical implications for interventions, that may be used to alleviate debilitating conditions (e.g., autism, schizophrenia), in which multisensory temporal function is shown to be impaired.